Characterization of a pH-Tolerant Strain Cobetia sp. SASS1 and Its Phenol Degradation Performance Under Salinity Condition - Mei, Rongwu; Zhou, Meng; Xu, Luning; Zhang, Yu; Su, Xiaomei (Frontiers in Microbiology, 2019)
Biological treatment of complex saline phenolic wastewater remains a great challenge due to the low activity of bacterial populations under stressful conditions. Acid mine drainage (AMD) as a typically extreme environment, shaped unique AMD microbial communities. Microorganisms survived in the AMD environment have evolved various mechanisms of resistance to low pH, high salinity and toxic heavy metals. The primary goal of this work was to determine whether a strain isolated from an AMD could degrade phenol under stressful conditions such as low pH, high salinity and heavy metals. The results suggested that the strain Cobetia sp. SASS1 isolated from AMD presented different physiological characteristics in comparison with five most closely related species. SASS1 can efficiently degrade phenol at wide ranges of pH (3.0-9.0) and NaCl concentration (0-40 g/L), as well as the existence of Cu2+ and Mn2+. Specifically, the SASS1 could completely degrade 1500 mg/L phenol in 80 h at 10 g/L NaCl. Meanwhile, mineralization of phenol was achieved with complete degradation of 900 mg/L phenol and simultaneously COD decreasing from 2239 mg/L to 181.6 mg/L in 36 h. Based on biodegradation metabolites identification and enzyme activities analysis, both ortho-cleavage pathway and benzoic acid pathway for phenol degradation were proposed. These findings suggested that SASS1 was an efficient phenol degrader under salinity and acidic conditions, and could be considered as key population for bioremediation of industrial phenolic wastewaters under stressful conditions.